If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-9y + -2z)(-8) = 0 Reorder the terms for easier multiplication: -8(-9y + -2z) = 0 (-9y * -8 + -2z * -8) = 0 (72y + 16z) = 0 Solving 72y + 16z = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-16z' to each side of the equation. 72y + 16z + -16z = 0 + -16z Combine like terms: 16z + -16z = 0 72y + 0 = 0 + -16z 72y = 0 + -16z Remove the zero: 72y = -16z Divide each side by '72'. y = -0.2222222222z Simplifying y = -0.2222222222z
| 1/16w^2+1/8w=1/2 | | 3d-4=d(d+8) | | 44x-4x=5x+18 | | -7-5x=5x+21 | | 10a+8b+4c-8d=7 | | 1-x=0.4 | | x^10=0.6 | | 6/7t=-48 | | 1-(x^10)=0.4 | | 5x-3=13-67 | | 2.8=14/x | | 2(r+5)=10-4r^2 | | 3t^3+5t=-8t^2 | | 2x^2y-5xy^2=0 | | (2x-3)(5x^2-2x+1)= | | z^2-20=22-z | | (-7x^3-2x-4)-(8x^2+4x-7)= | | 2x^2-6x+1=o | | 2p(p+4)=p^2+5p+10 | | 6y-8=40 | | 1/2+4/7p | | x+1.05x=20 | | -3(x+4)=24 | | 13c=2c^2+6 | | 64+x^3=0 | | -15-8b=9b+28 | | 0.5x-0.15=0.15 | | 10a^6/(2a^3) | | -6x+x^2+44.8*0.001=0 | | 0.24-2x=0.38 | | 6x+x^2+44.8*0.001=0 | | 5r(11r+6)=0 |